Kasus Malpraktik oleh Bidan yang Melakukan Kesalahan Persalinan di Rumah Sakit Riau Melalui Penerapan Restorative Justice Dihubungkan dengan Undang-Undang No. 36 Tahun 2009 Tentang Kesehatan - Rizky Muhammad Casesaria; Dey Ravena (UNISBA Press, 2023)
Abstract. Restorative justice is a settlement model that prioritizes recovery for victims, perpetrators, and society. The main principle of Restorative Justice is the participation of victims and perpetrators, the participation of citizens as facilitators in resolving cases, so that there is a guarantee that the child or perpetrator will no longer disturb the harmony that has been created in society. Restorative Justice aims to empower victims, perpetrators, families and communities to correct an unlawful act by using awareness and belief as a basis for improving social life explaining that the concept of Restorative Justice is basically simple. In carrying out health actions by health workers, namely nurses and midwives, it is possible for negligence to occur which can be fatal to the patient's soul and body, in legal or medical terms it is called malpractice. In article 29 of Law no. 36 of 2009 concerning health states that